2008
DOI: 10.1007/s00340-007-2896-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of diffuse reflections in tunable diode laser absorption spectroscopy: implications of laser speckle for gas absorption measurements

Abstract: The use of diffusely scattering materials as a means of eliminating interference fringes has been investigated. Their use introduces laser speckle that can contribute a random, rather than periodic, uncertainty to gas measurements. We have established a method for quantifying the uncertainty due to speckle and investigated ways of reducing it. We characterised the speckle at 823nm allowing the use of low cost CCD cameras. We have tested the principle of the model by making gas absorption measurements on the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The second possible source for the cell background is the laser speckle pattern on the detector, which is wavelength dependent. A detailed analysis of the laser speckle pattern caused by utilization of a diffuse reflector can be found in [9,10]. By applying the lens, many speckle points are integrated by the photodetector, with the effect that less intensity fluctuations appear on the transmission function when the laser wavelength is tuned [11].…”
Section: Design Of the Sensor Optics: Utilization Of A Diffuse Reflectormentioning
confidence: 99%
“…The second possible source for the cell background is the laser speckle pattern on the detector, which is wavelength dependent. A detailed analysis of the laser speckle pattern caused by utilization of a diffuse reflector can be found in [9,10]. By applying the lens, many speckle points are integrated by the photodetector, with the effect that less intensity fluctuations appear on the transmission function when the laser wavelength is tuned [11].…”
Section: Design Of the Sensor Optics: Utilization Of A Diffuse Reflectormentioning
confidence: 99%
“…A thrust of this research has been to improve the sensitivity by reducing the interference effects that occur from using narrow linewidth lasers. This has included assessing the effects of self-mixing interference from specular and diffuse reflections within the instrument [61] and investigating gas cell designs using diffuse reflectors [62] and integrating spheres [63,64], an example is shown in Fig. 31, and the issues associated with speckle that are introduced.…”
Section: Optical Gas Sensorsmentioning
confidence: 99%
“…We are investigating non-dispersive infrared (NDIR) techniques for the measurement of CO 2 [59] and formaldehyde and high resolution spectroscopy based on tuneable diode laser absorption spectroscopy (TDLAS) techniques to detect a range of gases including methane [60][61][62][63][64]. A thrust of this research has been to improve the sensitivity by reducing the interference effects that occur from using narrow linewidth lasers.…”
Section: Optical Gas Sensorsmentioning
confidence: 99%
“…In speckle interferometry these are termed correlation fringes and represent an intensity modulation of the randomised speckle field. We have previously demonstrated such an intensity modulation arising from a gas cell that uses a diffusely reflective surface [25] . Sirohi has shown that the intensity modulation at the detector takes the form [26] ;…”
Section: Interferometric Specklementioning
confidence: 99%